The Positive Influence of Satisfaction and Workload on Teachers Performance - Yuliani, Ratna; Harun, Cut Zahri; Yusrizal, Yusrizal (Journal of Education Reseach and Evaluation, 2022)
In today's age of globalization, education is very important. The educational provisions that society has developed well enough is undeniable, and the community will be increasingly qualified and able to compete competitively, as well as an era of increasingly fierce and tougher competition in various corners of life's activities. This study aims to analyze the impact of satisfaction and workload on improving teachers’ performance. This study uses quantitative research methods and data collection techniques used as interviews and questionnaires. The audiences in this study were all teachers in total 73 teachers. The analytical method was used to multiple linear regressions. The simultaneous test results also show that the variables of job satisfaction and workload have a significant effect on the performance of teachers by obtaining an F-count of 92.615. While F-table at the significant level α = 5% is 3.033. It shows, based on the statistical test F-count shows the F-count > F-table, with a probability level of 0.000. So, it can be concluded that satisfaction and workload have a positive influence on teacher performance.